(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: In a resource-limited and high burden disease setting, satisfied human resource is an asset in terms of high productivity, efficiency and quality care. Objective: To evaluate and analyze the employees’ job satisfaction at tertiary level hospitals and identify the important determinants for job satisfaction. Materials and Methods: This descriptive study was done in two leading specialized private owned hospitals of Bangladesh during January 2011 to April 2011. A group of 200 employees were selected from both clinical (60%) and non-clinical (40%) staffs through systematic sampling method. Self-administered structured questionnaire was used keeping focus on organizational supportive activities, management employee relationship, gender discrimination and overall job satisfaction. Results: Male and female participants were nearly equal, 75% female respondent was satisfied/highly satisfied on their job which was higher than male (55%)(P<0.005). Married participants and employees aged 31-40 years showed higher level of job satisfaction (P<0.005). Forty Four percent respondent considered that salary was not at expected level and 47% opined that they could participate very often in decision making process. Two third respondents considered that they enjoyed freedom in their job and majority (55%) admitted that they received praise for good work. All the respondents opined that they did not have any experience of sexual harassment. Univariate analysis was done to see the association between job satisfaction and other variables. Authority valued respondent’s contribution (P<0.005), satisfaction with salary and other benefits (P<0.005), superiors encourage employees about carrier development (p<0.005), make feeling about importance of job (P<0.005), receive praise for good work (P<0.05), superior looks after the personal welfare (P<0.05) and organization helps employee in their problem (P<0.005) were found significantly associated with Job satisfaction. Conclusion: To provide optimum health service by a health centre, all the staffs at all level, should be valued as an asset of the organization and their salary, participation and welfare should be properly looked after. Journal of Armed Forces Medical College Bangladesh Vol.11(2) 2015: 14-19